3D-printed custom implant for the management of “locked” posterior dislocation of the shoulder joint with reverse Hill-Sachs lesion: a case report - Hu, Yongrong; Yang, Kunhai; Liu, Hao; Wang, Liping; Wang, Song; Zhang, Xiang; Qu, Bo; Yang, Hongsheng (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Irregular bone defects of the humerus are common in clinical practice, but there are fewer reported cases of irregular humeral defects accompanied by shoulder joint "locking" dislocation and reverse Hill-Sachs injury caused by an electric shock. The choice of treatment for such cases is closely related to the extent of shoulder joint function recovery. This is a case report of a 60-year-old male patient who suffered from a shoulder joint "locking" dislocation with accompanying reverse Hill-Sachs injury due to muscle contraction after being electrically shocked at work. The patient was treated with a 3D-printed custom humeral head prosthesis for the treatment of the shoulder joint "locking" dislocation and reverse Hill-Sachs injury.Case presentation: A 60-year-old male patient, working as a construction worker, presented to our emergency department with right shoulder pain and restricted movement for more than 30 minutes after an electric shock. Right humeral CT revealed a comminuted fracture of the right humeral head. D-dimer levels were significantly elevated at 3239.00 ng/ml, and oxygen partial pressure was slightly decreased at 68 mmHg. Treatment included emergency wound debridement and dressing for the electrical injury, cardioprotective measures, anticoagulation, and symptomatic management.After stabilizing the patient's condition, the patient underwent 3D-printed custom prosthesisassisted partial replacement of the right humeral head and rotator cuff repair in the orthopedic department. Postoperatively, the patient's right shoulder joint wound healed well, and mobility was restored.This case report demonstrates that the use of a 3D-printed custom prosthesis for the treatment of irregular humeral bone defects caused by specific injury mechanisms, especially cases involving shoulder joint "locking" dislocation and reverse Hill-Sachs injury, can achieve precise bone defect repair, minimize surgical trauma, and provide superior outcomes in terms of postoperative functional rehabilitation.